The Art of Doing More with Less: Exploring Frugal Innovation Practices as Strategic Agility Drivers in SMEs - Ashari, Denny Rakhmad Widi; Waskita, Gautama Sastra (SINDA: Comprehensive Journal of Islamic Social Studies, 2025)
Small and medium-sized enterprises (SMEs) operating in resource-constrained environments often struggle to remain adaptive amid volatility, prompting the need for innovation approaches that enable agility despite structural limitations. This study examines how frugal innovation functions as a strategic driver of agility in SMEs, moving beyond its conventional framing as a cost-saving tactic. Using a qualitative research design involving semi-structured interviews, non-participant observations, and document analysis across selected SMEs, the study investigates the mechanisms that connect frugal innovation with strategic agility. The findings reveal three core mechanisms—strategic improvisation, resource recombination, and ecosystem engagement—that collectively enhance SMEs’ capacity to sense opportunities, respond swiftly, and reconfigure organizational processes. These mechanisms demonstrate that constraints can act as catalysts for adaptive capability rather than barriers to innovation. The study contributes to the theoretical integration of frugal innovation and strategic agility while offering practical insights for SME leaders, policymakers, and development institutions seeking to strengthen resilience and competitiveness. Broader implications highlight the role of frugal–agile practices in promoting inclusive and sustainable entrepreneurial ecosystems.